ISLAMIC COUNSELING TECHNIQUES - Rifqi Muhammad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2019)
This study aims to describe the names, forms and techniques of Islamic counseling from al-Ghazali's perspective. this type of research uses library research on the book of kimiya 'al-sa'adah by Imam al-Ghazali. The results of the study 1) al-Ghazali mentioned the name of the counseling formula with the term kimiya' al-sa'adah/spiritual chemistry; 2) the form of counseling done by al-Ghazali is spiritual counseling; 3) the counseling techniques used are self-knowledge questions; contemplation techniques; mirror technique; imagery technique.